Consumo de água do lírio asiático em vaso com diferentes substratos - Mello, Rosmary Panno (2006)
The purpose of the present study was to evaluate the water consumption in eight substrata: rice charred shell (CAC), ash of rice burned shell (CZ), coconut fiber (FC), soil of paradise (TP), TP+CAC, TP+CZ, FC+CAC and FC+CZ of Asian lily Orange Pixie in vase cultivation; to establish the best substrata for commercial production. The experiment was developed in the vegetation house of UFSM, Santa Maria, RS, during the period from May 17 to July 22, 2004. The experimental outlining was entirely casual by using 12 repetitions and three plants in each vase to determine the irrigation frequency and the water consumption for each substratum. In order to evaluate these parameters, limits were stipulated from at least 60% and at most 80% of the water retention capacity for the substratum in each vase being daily verified in digital scale. Due to the vegetative growing one vase of each treatment was destructed in five different periods of the lily development in order to readjust the weights of the vases in relation to the water consumption between the limits stipulated, besides establishing the evolution of the dry fitomass on aerial portion, bulbs and roots. The determinations accomplished on substrata were: the substratum density, the total porosity, the aerial space and the water availability as physics characteristics as well as the hydrogen potential, the total tenor of soluble salts and the capacity of cations exchange as chemical characteristics. In the vegetal were determined the height of the plant and of the first flower insertion, the area of the leaf, the size of the leaf, the number of flowers and leafs, the total consumption of water and the irrigation frequency. The results have showed that the Asian lily Orange Pixie in vase adapts for commercial cultivation by using 50% in volume of CAC in the substrata composition with FC and TP.